Correlation of C-reactive protein and BMI with severity of diabetic retinopathy - Naveen Nishal G; Renuga Devi Kaliaperumal; Nallamuthu P; Subhashini M (Asian Journal of Medical Sciences, 2022)
Background: Diabetic retinopathy is one of the complications of diabetes mellitus (DM). The pathogenesis has been attributed to be due to inflammation recently. Similarly, obesity has been found to be risk factor for diabetic retinopathy. Aims and Objectives: The aim of the study was to evaluate the changes of C-reactive protein (CRP) in Type 2 DM patients with diabetic retinopathy and to evaluate the relationship of body mass index (BMI) with diabetic retinopathy. Materials and Methods: This was a hospital-based cross-sectional study of 98 patients with Type 2 DM both newly diagnosed and known case of DM. The patient’s fundus findings were recorded, CRP and BMI were measured to study the correlation. Results: This study showed that the mean value of CRP in patient without diabetic retinopathy was 2.28 mg/L while it was 3.01 mg/L in patients with diabetic retinopathy. Among the patients with diabetic retinopathy, the mean CRP was 2.76 mg/L in NPDR, 2.93 mg/L in NPDR with CSME, 3.6 mg/L in PDR, and 3.9mg/L in PDR with CSME. The mean BMI was 22.63 Kg/m² in patients without diabetic retinopathy and 22.92 Kg/m² in patients with diabetic retinopathy. Conclusion: The study shows that CRP levels correlate with stage of diabetic retinopathy. The higher levels CRP were found in patients with PDR and CSME presumably due to the higher level of inflammatory activity in retina. Further our study found no correlation of BMI with diabetic retinopathy.